Language and Cognitive Impairment Associated with a Novel p.Cys63Arg Change in the MED13L Transcriptional Regulator - Jiménez-Romero, Salud (Mol Syndromol, 2018)
Mutations in the MED13L gene, which encodes a subunit of a transcriptional regulatory complex, result in a complex phenotype entailing physical and cognitive anomalies. Deep language impairment has been reported in affected individuals, mostly in patients with copy number variations. We report on a child with a nonsynonymous p.Cys63Arg change in MED13L (chr12:116675396A>G, GRCh37) who exhibits profound language impairment in the expressive domain, cognitive delay, behavioral disturbances, and an autism-like phenotype. Because of the brain areas in which MED13L is expressed and because of the functional links between MED13L and the products of selected candidate genes for cognitive disorders involving language deficits, the proband's linguistic phenotype may result from changes in a functional network important for language development and evolution.